The Impact of Post-Synthetic Linker Functionalization of MOFs on Methane Storage: The Role of Defects - Szilágyi, Petra Ágota; Serra-Crespo, Pablo; Gascon, Jorge; Geerlings, Hans; Dam, Bernard (Frontiers in Energy Research, 2016)
Natural gas is increasingly being viewed as one of the most viable alternatives to gasoline. However, its vehicular application will only be widespread if safe and high-capacity methane stores are developed. In this work, we report an over 33% increase in methane uptake on a post-synthetically modified metal–organic framework. The underlying mechanism for this dramatic increase is due to lattice defects formed upon post-synthetic modification. This method may open new approaches to natural gas storage.